1998
DOI: 10.1002/(sici)1096-8652(199806)58:2<105::aid-ajh3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cytarabine, and G-CSF (FLAG) for the treatment of poor risk acute myeloid leukemia

Abstract: Thirty-eight patients with primary resistant or relapsing acute myeloid leukemia (AML) were treated with fludarabine, cytarabine and granulocyte colony-stimulating factor (FLAG). Median age was 41 (range 11-70). Sixteen patients had AML that was primary resistant to induction treatment, while 22 were relapsed, 11 after autologous bone marrow transplant (AuBMT), 8 less than 6 months from complete remission (CR) achievement, and 3 were second relapse from chemotherapy alone. Overall, 21 of 38 patients (55%) obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 20 publications
6
56
2
2
Order By: Relevance
“…Several studies have indeed demonstrated that the in vitro sensitivity to cytarabine of AML cells could be enhanced by preincubation with granulocyte colony-stimulating factor (G-CSF) and/or with granulocyte -macrophage colony-stimulating factor (GM-CSF) (Butturini et al, 1990;Bai et al, 1999). Clinically, pretreatment with G-CSF (as in the FLAG regimen, which is a combination therapy of fludarabine, cytarabine, and G-CSF), seems to be effective and well tolerated in the treatment of poorrisk AML patients (Montillo et al, 1998;Jackson et al, 2001). The efficacy of this therapy, however, has not yet been determined in a controlled, randomised clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indeed demonstrated that the in vitro sensitivity to cytarabine of AML cells could be enhanced by preincubation with granulocyte colony-stimulating factor (G-CSF) and/or with granulocyte -macrophage colony-stimulating factor (GM-CSF) (Butturini et al, 1990;Bai et al, 1999). Clinically, pretreatment with G-CSF (as in the FLAG regimen, which is a combination therapy of fludarabine, cytarabine, and G-CSF), seems to be effective and well tolerated in the treatment of poorrisk AML patients (Montillo et al, 1998;Jackson et al, 2001). The efficacy of this therapy, however, has not yet been determined in a controlled, randomised clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the principal clinical and diagnostic data of patients. The Table 1 Principal clinical characteristics of patients older than 60 years who underwent PBSC autotransplant following myeloablative therapy 16 for multiple myeloma, FLAG 17 at reduced dose for AML, the GIMEMA protocol for ALL or byphenotypic leukemia 18 and a combination of cisplatinum and vinorelbin for lung carcinoma. Patient status at PBSC autotransplant was relapse for eight patients (seven lymphomas, one myeloma), resistance for eight patients (two lymphomas, four myelomas, one carcinoma and one Waldenstrom's disease), complete remission for three patients (two leukemias and one myeloma).…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41][42] Thus, on the basis of the current analyses, the assignment of salvage regimens to patients with refractory and relapsed AML should be stratified not only with regard to the duration of the first CR but also with regard to chromosome abnormalities. Further patients should be evaluated to add to the current data and also to clarify the role of chromosome abnormalities determined directly prior to salvage therapy which are different to the initial karyotype in about 60% of cases.…”
Section: Figurementioning
confidence: 99%